RADON CAN DETECT POTENTIAL NATURAL DISASTERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 Although radon is a radioactive gas which can cause lung cancer in instances of overexposure, it can also foretell the onset of natural disasters. A physicist from Universiti Sains Malaysia (USM) specialising in radiation, Professor Dr. Mohamad Suhaimi Jaafar stated that to date most studies on radon tended to focus on its harmful effects on human beings.